Urban Heat Islands: Green Roofs as a Potential Way to Attenuate Temperatures in Cities - Romero, Juliana (My University, 2024)
The excessive construction and the destruction of green spaces have had notable consequences on the environment within cities. Under this context, green roofs have been proposed to attenuate these issues and to achieve sustainable building practices. In this paper, technical and construction aspects of green roofs are used to classify different systems. By reviewing the benefits related to the mitigation of the urban heat island effect, reduction in building energy consumption, improvement of air pollution, water management and increase in sound insulation, among others, this paper shows how green roofs may contribute to more sustainable buildings and cities. It is expected that this paper may not only propose a solution, but it may also raise awareness of the importance of urban greenery.

La construcción excesiva y la destrucción de espacios verdes han tenido consecuencias notables en el medioambiente dentro de las ciudades. En este contexto, los techos verdes han sido propuestos para atenuar estos problemas y lograr edificios sostenibles. En este artículo, se utilizan aspectos técnicos y constructivos de los techos verdes para clasificar diferentes sistemas. Al examinar los beneficios relacionados con la mitigación del efecto isla de calor urbano, la reducción del consumo de energía de los edificios, la mejora de la contaminación del aire, la gestión del agua y el aumento del aislamiento acústico, entre otros, este documento muestra cómo los techos verdes pueden contribuir a que los edificios y las ciudades sean más sostenibles. Se espera que este documento no sólo pueda proponer una solución, sino también generar conciencia sobre la importancia del verdor urbano.
Keywords: Inglés II; sustainable construction; urban greenery; urban heat islands; green roofs; construcción sostenible; verdor urbano; islas de calor urbanas; techos verdes